Structure–property relationship of halloysite nanotubes/ethylene–vinyl acetate–carbon monoxide terpolymer nanocomposites. (January 2017) - George, Gibin; Selvakumar, M; Mahendran, Arunjunairaj; Anandhan, S
Poly(ethylene- co -vinyl acetate- co -carbon monoxide) (EVACO)/halloysite nanotube (HNT) nanocomposite films were solution cast. Dispersion of HNTs in the matrix was analyzed by elemental mapping and the role of HNTs on crystallizability, flammability and thermal, mechanical, and electrical properties of the polymer was evaluated. The nature of interaction between the EVACO matrix and HNTs was studied using Fourier transform infrared spectroscopy. The highest tensile strength was observed for the composite with 1% filler loading, whereas the highest crystallinity was observed for that with 3% filler loading. The decay in the tensile properties at higher filler loading was due to agglomeration of HNTs and debonding of polymer–filler interface. The electrical volume resistivity of the composites decreased with HNT loading because of the ionic charge transfer. The direct current electrical resistivity study of the composites proves that the addition of HNT can improve the antistatic properties of the polymer.